Implementation of Input Shaping in Hybrid Control Schemes of a Lab-Scaled Rotary Crane System - Mohd Ashraf, Ahmad; Mohd Syakirin, Ramli; Mohd Anwar, Zawawi; Raja Mohd Taufika, Raja Ismail (2010)
This paper presents investigations into the implementation of input shaping techniques in hybrid control schemes of a rotary crane system. A lab-scaled rotary crane is considered and the dynamic model of the system is derived using Euler-Lagrange formulation. To study the effectiveness of the controllers, initially a collocated proportional-derivative (PD) control is developed for horizontal angle position control of rotary crane. This is then extended to incorporate input shaping techniques for anti-swaying control of the system. The positive and modified Specified Negative Amplitude (SNA) input shaping with different derivative orders respectively were designed based on the properties of the system. Implementation results of the response of the rotary crane with the controllers are presented in time and frequency domains. The performances of input shaping in hybrid control schemes are examined in terms of level of input tracking capability, swing angle reduction, and time response specifications. Finally a comparative assessment of the control techniques is discussed and presented.